Potensi minuman bubuk kedelai (var. Galunggung) sebagai minuman fungsional: sifat fisikokimia, efek hipoglikemik dan hipokolesterolemik serta status antioksidan - Setyaningrum Aviriani; Sri Handajani; Dian Rachmawanti Affandi; Endang Listyaningsih (Jurnal Gizi Klinik Indonesia, 2012)
Background: Powdered soy beverage is one of the functional drink products that grow rapidly in Indonesia. The beverage comes with variety of health claims including lower blood glucose level and improve antioxidant status. Galunggung is one of Indonesian superior soybean varieties that have several advantages, such as leave rust resistant, productivity reached 1,5 tons/ha, can be cultivated in tidal lands, large seeds and sturdy pods.Objective: To determine the potential of powdered soybean (var. Galunggung) beverage as functional drink observed from physicochemical characteristics and effect of intake on glucose and cholesterol levels and antioxidant status of diabetic-hypercholesterolemic rats. Method: The physicochemical characteristics evaluation performed by measuring disperse-ability, nutritional quality (proximate analysis), dietary fi ber and in vitro antioxidant capacity (total phenol content and anti radical DPPH activity). Determination of powdered soybean (var. Galunggung) beverage effectiveness to decrease plasma glucose and cholesterol levels and improve antioxidant status were conducted using 18 Sprague-Dawley male rats aged 3 months with an average body weight of 150 g, divided into three groups: negative control (placebo), positive control (diabetichypercholesterolemia) and treatment (powdered soybean beverage diet) group.Result: Powdered soybean (var. Galunggung) beverage showed comparable physicochemical characteristics to commercial powdered soy beverage. This beverage also showed hypoglycaemic and hypocholesterolemic effects, and improve antioxidant status of diabetic-hypercholesterolemic rats. Plasma glucose level of diabetic-hypercholesterolemic rats decreased from 228.03 + 2.55 mg/dl to 123.33 ± 1.89 mg/dl, plasma cholesterol level reduced from 177.08 ± 4.64 mg/dl to 119.69 ± 2.95 mg/dl and plasma MDA levels declined from 12.01 + 0.41 mmol/l to 5.50 + 0.20 mmol/l after intervention with powdered soybean (var.Galunggung) beverage diet for 2 weeks.Conclusion: Powdered soybean (var. Galunggung) beverage has the potential to be developed as functional drink with several health claims, i.e. reduce glucose and cholesterol levels, and improve antioxidant status.